Composition in three keys: art, nature, and science - Barbara Gleason; Mark Wiley (Ilha do Desterro)
Imagine you are at a cocktail party hosted by your college and attended by people from a variety of academic disciplines. Eventually a colleague corners you and inquires: "So, what's your area?" And you unthinkingly reply, "Composition!" From some experience the very next question is usually, "Oh, 'composition.' What's that?" We'll let you imagine the tone and emphasis with which this last question might be asked. But whatever the tone, you feel obligated to respond.